Nanotechnology based drug delivery systems for malaria - Keles, Sedanur; Alakbarli, Jahid; Akgul, Busra; Baghirova, Malahat; Imamova, Nergiz; Barati, Ana; Shikhaliyeva, Inji; Allahverdiyev, Adil (ELSEVIER, 2024)
Malaria, caused by Plasmodium parasites transmitted through Anopheles mosquitoes, remains a global health burden, particularly in tropical regions. The most lethal species, Plasmodium falciparum and Plasmodium vivax, pose significant threats to human health. Despite various treatment strategies, malaria continues to claim lives, with Africa being disproportionately affected. This review explores the advancements in drug delivery systems for malaria treatment, focusing on polymeric and lipid-based nanoparticles. Traditional antimalarial drugs, while effective, face challenges such as toxicity and poor bio-distribution. To overcome these issues, nanocarrier systems have been developed, aiming to enhance drug efficacy, control release, and minimize side effects. Polymeric nanocapsules, dendrimers, micelles, liposomes, lipid nanoparticles, niosomes, and exosomes loaded with antimalarial drugs are examined, providing a comprehensive overview of recent developments in nanotechnology for malaria treatment. The current state of antimalarial treatment, including combination therapies and prophylactic drugs, is discussed, with a focus on the World Health Organization's recommendations. The importance of nanocarriers in malaria management is underscored, highlighting their role in targeted drug delivery, controlled release, and improved pharmacological properties. This review bridges the gap in the literature, consolidating the latest advancements in nanocarrier systems for malaria treatment and offering insights into potential future developments in the field.
Keywords: Malaria; Drug delivery system; Nanotechnology; Polymeric nanoparticles; Lipid nanoparticles; Antimalarial drugs; NANOSTRUCTURED LIPID CARRIERS; ARTEMETHER-LUMEFANTRINE; ANTIMALARIAL; NANOCAPSULES; EFFICACY; PHARMACOKINETICS; NANOCARRIERS; FORMULATION; LIPOSOMES; Pharmacology & Pharmacy